2006
DOI: 10.1007/s11270-006-1808-x
|View full text |Cite
|
Sign up to set email alerts
|

Transport Of Fecal Bacteria From Poultry Litter and Cattle Manures Applied to Pastureland

Abstract: Land applications of manure from confined animal systems and direct deposit by grazing animals are both major sources of bacteria in streams. An understanding of the overland transport mechanisms from land applied waste is needed to improve design of best management practices (BMPs) and modeling of nonpoint source (NPS) pollution. Plots were established on pasturelands receiving phosphorus-based livestock waste applications to measure the concentrations of Escherichia coli (E. coli), fecal coliform (FC), and E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
74
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(81 citation statements)
references
References 16 publications
6
74
0
1
Order By: Relevance
“…For example, Animal waste can enter water bodies from leaking or overflowing waste lagoons or through runoff from fields amended with animal manure [1][2][3][4]. In many watersheds, wildlife such as geese and deer are a significant source of E. coli [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Animal waste can enter water bodies from leaking or overflowing waste lagoons or through runoff from fields amended with animal manure [1][2][3][4]. In many watersheds, wildlife such as geese and deer are a significant source of E. coli [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have attempted to quantify the amount of indicator bacteria transported in runoff from pastures where animal waste has been applied (Doran and Linn 1979;Edwards et al 2000;Kunkle 1970;Soupir et al 2006) and from feedlots (Miner et al 1966;Young et al 1980). Moore et al (1988) summarized several researches reporting indicator bacteria concentration in runoff from pasture, grazing systems, cropland and feedlot.…”
Section: Introductionmentioning
confidence: 99%
“…In lab studies, the simulated field runoff from turkey litter-amended plots has been shown to contain 1.3 ϫ 10 4 CFU 100 ml Ϫ1 of E. coli, 1.8 ϫ 10 4 CFU 100 ml Ϫ1 of fecal coliforms, and 6.6 ϫ 10 3 CFU 100 ml Ϫ1 of Enterococcus spp. (45).…”
mentioning
confidence: 99%